THE INFLUENCE OF TAX KNOWLEDGE, TAXPAYER AWARENESS, AND TAX SANCTIONS ON TAXPAYER COMPLIANCE: THE MODERATING ROLE OF SERVICE QUALITY AT KPP PRATAMA NGAWI - Erwin Nur Kurotin; Ikhsan Budi Riharjo (JAT : Journal Of Accounting and Tax, 2026)
Tax is a main source of state revenue that is used to finance national development. This study investigates and analyses the effect of tax knowledge, taxpayers’ awareness, and tax sanction on personal taxpayers’ compliance, with service quality as a moderating variable in Ngawi Pratama Tax Service Office (KPP). Furthermore, the study applies quantitatively with a causal- associative method. The population consists of active personal taxpayers listed on Ngawi Pratama KPP. Moreover, the data were collected using simple random sampling. In line with that, 92 respondents as the samples with Slovin formula. The data were primary and in the form of a questionnaire. The questionnaires were distributed online. Additionally, moderation regression was applied as the data analysis technique. As a result, it shows that both tax knowledge and taxpayers’ awareness have a positive effect on taxpayers’ compliance. In contrast, tax sanction does not affect taxpayers’ compliance. In addition, service quality is proven to be able to moderate the effect of taxpayers’ awareness and tax sanction on taxpayers’ compliance. However, it cannot moderate the effect of tax knowledge on taxpayers’ compliance. These findings indicate that the incline of tax service quality can strengthen the effectiveness of some factors which support taxpayers’ compliance. In addition, this research is expected to contribute to the development of tax policy and become an evaluation for tax authorities in increasing taxpayers’ compliance continually.